Pharmacists Without Access to the EHR: Practicing with One Hand Tied Behind Our Backs - Deeatra S. Craddock; Ronald G. Hall (University of Minnesota Libraries Publishing, 2021)
Pharmacists are the most accessible healthcare professionals to the public, yet have the least amount of information from the electronic health record available to them. This lack of information makes ensuring that patients are receiving proper medications and monitoring for efficacy and safety a challenge, if not impossible in some situations. Having access to a national electronic health record would provide pharmacists with this needed information to truly engage with prescribers as fellow clinical experts in the field. Sharing prescription information for non-controlled substances would also decrease the likelihood of a patient receiving duplicative therapy from two prescribers or pharmacies that may not know what the other is doing. There are already examples of successful national data sharing including the Prescription drug Monitoring Program for controlled substances as well as the Veterans Affairs healthcare system. Therefore, our profession needs to push for nationwide access to patient electronic health records, which includes all healthcare providers. This will facilitate the inclusion of pharmacists in the optimization of the care of patients who need our expertise in managing their medication regimens as well as build better relationships with prescribing providers.